The cool bean [book with audioplayer] - John, Jory ([Library Ideas, LLC], 2020)
Everyone knows the cool beans. They're sooooo cool. And then there's the uncool has-bean ... Always on the sidelines, one bean unsuccessfully tries everything he can to fit in with the crowd--until one day the cool beans show him how it's done.